Effects of protein-calorie malnutrition on endocrine pancreatic function in young pregnant rats. - de-Mello, M. A.; Cury, L. (My University, 1989)
Oral glucose tolerance test (GTT), insulin secretion after oral glucose load and the insulin to glucose ratio (I/G) during GTT were measured in young (45-50 days old) pregnant and non-pregnant rats fed a normal (25%) or low (6%) protein diet during pregnancy or for a 22-day period. Fasting blood glucose was lower in protein-deficient rats and basal plasma insulin was higher in pregnant control rats than in non-pregnant controls. Protein-deficient rats were intolerant to the oral glucose load. The I/G ratio during GTT was higher in control pregnant rats than in other rats. These results show that young malnourished pregnant rats are glucose intolerant and do not show pregnancy hyperinsulinemia probably as a result of decreased pancreatic capacity to release insulin in response to stimulation.